Deep eutectic solvent stabilised Co–P films for electrocatalytic oxidation of 5-hydroxymethylfurfural into 2, 5-furandicarboxylic acid. (12th August 2020) - Kang, Myung Jong; Yu, Hye Jin; Kim, Hyun Sung; Cha, Hyun Gil
Abstract : The Co–P electrode synthesized in deep eutectic solution showed enhanced stability for electrocatalytic HMF oxidation into FDCA. Abstract : The electrocatalytic oxidation of 5-hydroxymethylfurfural (HMF) into 2, 5-furandicarboxylic acid (FDCA) has been studied extensively. However, the short lifetime of catalytic electrodes remains a challenge for the electrocatalytic HMF oxidation reaction, and the high pH of the electrolyte causes denaturation of HMF during the reaction. Herein, deep eutectic solvents (DES) are employed for the preparation of efficient and durable catalytic electrodes for HMF oxidation. The catalytic electrode made up of DES avoided the complexity of multiple alkylations leading to 99% HMF conversion affording FDCA in 85.3% yield with high durability, due in part to the lower pH of the electrolyte.